2019
DOI: 10.1126/sciimmunol.aap9520
|View full text |Cite
|
Sign up to set email alerts
|

Impaired enolase 1 glycolytic activity restrains effector functions of tumor-infiltrating CD8 + T cells

Abstract: In the context of solid tumors, there is a positive correlation between the accumulation of cytotoxic CD8+ tumor infiltrating lymphocytes (TILs) and favorable clinical outcomes. However, CD8+ TILs often exhibit a state of functional exhaustion limiting their activity, and the underlying molecular basis of this dysfunction is not fully understood. Here, we show that TILss found in human and murine CD8+ melanomas are metabolically compromised with deficits in both glycolytic and oxidative metabolism. While sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 60 publications
6
80
0
Order By: Relevance
“…To this end, we studied the impact of PDK4-deficiency on the development of EAE, an autoimmune disease induced by pathogenic Th17 cells. Consistent with previous studies that glycolysis promotes inflammation [57], [69]- [71], mice with global knockout of PDK4 developed less severe disease as determined by the clinical disease scores ( Figure 3H) with decrease in Th17 cells and increase in the infiltration of Foxp3 + Tregs in the CNS of the mice undergoing EAE (Figure 3I). We therefore conclude that PDK4-deficient Th17p cells resemble Th17n in their central carbon metabolic state, but not in other metabolic pathways.…”
Section: Pdk4-deficient Th17p Cells Adopt a Non-pathogenic-like Centrsupporting
confidence: 91%
See 1 more Smart Citation
“…To this end, we studied the impact of PDK4-deficiency on the development of EAE, an autoimmune disease induced by pathogenic Th17 cells. Consistent with previous studies that glycolysis promotes inflammation [57], [69]- [71], mice with global knockout of PDK4 developed less severe disease as determined by the clinical disease scores ( Figure 3H) with decrease in Th17 cells and increase in the infiltration of Foxp3 + Tregs in the CNS of the mice undergoing EAE (Figure 3I). We therefore conclude that PDK4-deficient Th17p cells resemble Th17n in their central carbon metabolic state, but not in other metabolic pathways.…”
Section: Pdk4-deficient Th17p Cells Adopt a Non-pathogenic-like Centrsupporting
confidence: 91%
“…The most notable of these reactions was the one catalyzed by the enzyme phosphoglycerate mutase (PGAM), which was negatively associated with pathogenicity in the intra-population analysis of Th17n cells ( Figure 4A), but positively associated with Th17p cells in the inter-population analysis ( Figure 2B,C). This prediction was unexpected because increased glycolysis is generally known to support pro-inflammatory phenotypes in T cells (see also Discussion) [55]- [57], [69], [72]- [78].…”
Section: The Glycolytic Enzyme Phosphoglycerate Mutase (Pgam) Suppresmentioning
confidence: 97%
“…Similarly, Chen et al showed that the expression of B7-H4 on esophageal cancer cells is inversely correlated with the densities of CD8+ TILs, suggesting that B7-H4 inhibits TILs recruitment (23). In addition, the impaired function of CD8+ TILs may also be mediated by immunosuppressing factors released by tumor cells, deficient presentation of tumor antigen by dendritic cells, and reduced production of co-stimulating cytokines by helper CD4+ T-cells (42,43).…”
Section: Discussionmentioning
confidence: 96%
“…Th17 cells are heavily dependent on glycolysis for their development and maintenance 13,14,30 . Likewise, anergic T cells and dysfunctional tumor infiltrating lymphocytes are reported to have defects in glycolytic pathway [31][32][33] and deficiency in glucose transporter glut1 has been linked with decreased effector function and protection from inflammatory diseases 34 . We detected reduction in expression of glucose transporter Glut3 (GEO accession GSE128308) in addition to all the transcripts encoding enzymes glycolytic enzymes leading us to conclude that FGIN-1-27 treatment alters the glycolytic pathway in Th17 cells, thus demonstrating that a small molecule can be used to alter the glycolytic machinery in a cell to achieve a desirable immune response.…”
Section: Discussionmentioning
confidence: 99%